A value chain analysis of two fruit and vegetable production hubs in south-Benin - Egah, Janvier; Termeer, Emma; Dijkxhoorn, Youri; Raoult, Justine (CGIAR, 2024)
Key Findings • Inadequate packaging, poor road conditions and lacking infrastructure in both hubs lead to high transportation costs and significant post-harvest losses, impacting the profitability and efficiency of the value chain. • Trust issues between farmers and traders, particularly regarding credit transactions, lead to conflicts and financial losses. • The use of chemical fertilizers results in poor quality produce, which accelerates spoilage. Combined with the lack of proper storage facilities, this makes it difficult to maintain the quality of produce until it reaches consumers.